Innovation in Islamic Religious Education Learning Through the Utilization of Educandy Interactive Game Media - Saehu Abas; Mohamad Alwi; Elis Siti Maria Ulfah; Ahmad Ali; Ahmad Zuhair Syafiq; Vikria Vikria (FASHLUNA, 2026)
This study aims to improve students’ cognitive learning outcomes in Islamic Religious Education (IRE) through the use of the Educandy interactive game. This study was motivated by low student learning outcomes caused by the dominance of conventional teaching methods that are unengaging and not fully aligned with student characteristics in the digital age. The research method employed was Classroom Action Research (CAR) using the Kemmis and McTaggart model, conducted in two cycles, encompassing the planning, implementation, observation, and reflection stages. The research subjects were 10th-grade students at SMK Al-Hidayah Cirebon during the odd semester of the 2025/2026 academic year. Data collection techniques included cognitive tests, observation of student activities, interviews, and documentation. The research results indicate that the implementation of the Educandy interactive media significantly improved students’ cognitive learning outcomes. This improvement is evidenced by an increase in the class average score from 58.4 (pre-cycle) to 71.6 (Cycle I), and finally to 81.4 in Cycle II. In line with this, the percentage of mastery in traditional learning increased from 34.3% to 51.4% in Cycle I, and reached 80.0% in Cycle II, successfully exceeding the predetermined success indicator (≥ 75). This increase was driven by the media familiarity effect, increased engagement in group learning, and a healthy competitive environment introduced by the leaderboard feature.